Patch test results with fragrance markers of the baseline series - analysis of the European Surveillance System on Contact Allergies (ESSCA) network 2009-2012 - Frosch, Peter J.; Johansen, Jeanne Duus; Schuttelaar, Marie-Louise A.; Silvestre, Juan F.; Sanchez-Perez, Javier; Weisshaar, Elke; Uter, Wolfgang (Contact Dermatitis, 2015)
Contact allergy to fragrances is common, and impairs quality of life, particularly in young women.To provide current results on the prevalences of sensitization to fragrance allergens used as markers in the baseline series of most European countries.Data of patients consecutively patch tested between 2009 and 2012 in 12 European countries with fragrance allergens contained in the baseline series were collected by the European Surveillance System on Contact Allergies network and descriptively analysed. Four departments used the TRUE Test(®) system.The 'basic markers' were tested on 51 477 [fragrance mix II (FM II)] to 57 123 [Myroxylon pereirae, balsam of Peru] patients, and yielded positive reactions as follows: fragrance mix I 6.9%, Myroxylon pereirae 5.4%, FM II 3.8%, colophonium 2.6%, and hydroxyisohexyl 3-cyclohexene carboxaldehyde 1.7%, with some regional differences. Prevalences with TRUE Test(®) allergens were lower. Additional fragrances were tested on 3643 (trimethylbenzenepropanol) to 14 071 (oil of turpentine) patients, and yielded between 2.6% (Cananga odorata) and 0.7% (trimethylbenzenepropanol) positive reactions.Contact allergy to fragrances is common throughout Europe, with regional variation probably being explained by patch test technique, and differences in exposure and referral patterns. The current basic markers of fragrance sensitivity in the baseline series should be supplemented with additional fragrance allergens.
EVALuna2:5515